Training Rats Using Water Rewards Without Water Restriction - Reinagel, Pamela (Frontiers in Behavioral Neuroscience, 2018)
High-throughput behavioral training of rodents has been a transformative development for systems neuroscience. Water or food restriction is typically required to motivate task engagement. We hypothesized a gap between physiological water need and hedonic water satiety that could be leveraged to train rats for water rewards without water restriction. We show that when Citric Acid (CA) is added to water, female rats drink less, yet consume enough to maintain long term health. With 24 hour/day access to a visual task with water rewards, rats with ad lib CA water performed 84%±18% as many trials as in the same task under water restriction. In 2-hour daily sessions, rats with ad lib CA water performed 68%±13% as many trials as under water restriction. Using reward sizes <25ul, rats with ad lib CA performed 804±285 trials/day in live-in sessions or 364±82 trials/day in limited duration daily sessions. The safety of CA water amendment was previously shown for male rats, and the gap between water need and satiety was similar to what we observed in females. Therefore it is likely that this method will generalize to male rats, although this remains to be shown. We conclude that at least in some contexts rats can be trained using water rewards without water restriction, benefiting both animal welfare and scientific productivity.